Coronary Angiographic Findings Among the Left Bundle Branch Block Patients - Iqbal, Abu Tarek; Ayub, Md; Salehuddin, Md; Ahmed, Khurshed (University Heart Journal, 2018)
Introduction: Complete Left bundle branch block(LBBB) increases the risk of cardiac mortality, and prognosis is primarily determined by the underlying coronary artery diseases. The goal of this study was to determine the association of complete left bundle branch block (LBBB), with site, severity & risk factors of coronary artery disease (CAD) diagnosed by coronary angiogram(CAG). Methods: A total of 75 symptomatic patients with LBBB were evaluated in a one year period by coronary angiography in a tertiary care hospital of Chittagong, Bangladesh. Standard protocol and procedure were followed during doing both ECG and CAG. All data were compiled and were analyzed by SPSS-20. Results: Among 75 patients analyzed male were 40(53.3%) and female was 35(46.67%). Male to female ratio was 1:1.14.. Among all 22(29.33%) patients were at age group <60 years, 48(64%) were at age group 40-60 years and 5(6.6%) were <40 years of age. 34(45.3%) patients were from rural community. Regarding risk factor analysis 19(25.2%) patients had DM, 16(21.33%) patients had different kinds of dyslipidemia, 8(10.6%) patients were obese, 3(4%) patients had high cholesterol(>400mg/dl), 26(34.66%) patients were hypertensive, 21(28%) were smoker, 2(2.66%) were taking jarda, 8(10.6%) patients had family history of coronary artery disease and one patients had history of alcoholism. Angiographic study revealed 6(8%) had single vessel disease, 16(21.33%) had double vessel disease, 5(6.66%) had triple vessel disease and 48(64.00%) patients had normal vessels. Conclusion: LBBB may be assoictaed with normal to variable involvement of coronary artery University Heart Journal Vol. 12, No. 2, July 2016; 88-90